Administrative reform policy: the case of Norway - Christensen, Tom; Loegreid, Per (1998)
This article outlines a number of perspectives on the development of Norway's administrative policy. The content of the renewal and modernization programmes in Norwegian public administration in the 1980s will be analysed and related to traditional, administrative values, as well as to the trend towards the New Public Management (NPM) and other more specific changes in central public administration in the last decade. The article present some results from a survey conducted in 1996, focusing on the relevance and effects of some of the more recent reforms in central public administration. The article concludes by discussing the Norwegian way of reforming public administration and the implications for administrative policy
Keywords: Administrative reform - Norway; Administrative reform